The Ninth Malaysia Plan (9MP) announcement effect on Government Linked Corporation’s (GLC’s) stock price: a test of semi strong-form efficiency on Bursa Malaysia / Norliza Abu Hassan - Abu Hassan, Norliza (2006)
Over the last two decades prior to the late 1970s, a rich body of literature developed substantiating the general validity of Efficient Market Hypothesis (EMH). However, finding from the recent work, particularly in the 1980s have not reached a consistent conclusion (although evidence supporting EMH, is continually documented.). Since the late 1970s, the persistent documentation of stock market anomalies and thus evidence of inefficiencies have posed a current challenge to EMH and has put EMH on notice. These anomalies include size effects, turn of the year effects, low P/E ratio effects, week-end effects and performance of low-beta portfolios. The semi-strong version of Efficient Market Hypothesis (EMH) posits that all publicly information is impounded, as soon as it becomes available, in share prices. This implies that since all publicly available information issued by the market in assessing expected future (returns) prices, an investor cannot use publicly available information as the basis for a trading strategy to earn abnormal returns. Public information includes current as well as past market information.